Consumo y costo del haloperidol y ziprasidona por via oral en el servicio de salud mental del hospital nacional edgardo rebagliati martins - essalud lima, en el periodo julio - diciembre 2008” - Acevedo Rios, Manuel Eutimio (2009)
The present descriptive, transverse, and retrospective study, had as objective to determinate the characteristics of consume and cost of Haloperidol and Ziprasidone by oral road in the mental health service of the National Hospital Edgardo Rebagliati Martins - ESSALUD in the period on July - December, 2008. The sample in study was shaped by the Units of haloperidol and Ziprasidone prescribed in mental health during this period, it was investigates: consume monthly and half yearly of Haloperidol and Ziprasidone expressed in daily definite dose (DDD) for 100 beds – days, in addition monthly and half year consumer expenditure. The Haloperidol and Ziprasidone consume in the National Hospital Edgardo Rebagliati Martins - ESSALUD during July - December, 2008 was 63,80 and 18,28 respectively, that generated an cost of S/. 43461.6 for the Haloperidol and S/. 76010,0 for the Ziprasidone